2011
DOI: 10.1080/00222933.2011.587899
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of terrestrial isopods in a protected area characterized by salty coastal ponds (Vendicari, Sicily)

Abstract: The diversity of Oniscidean isopods was studied in Vendicari, a protected area in southeastern Sicily characterized by salty ponds separated from the sea by narrow bands of land. Samples were collected in pitfall traps placed in transects from the coastline to the ponds and from the ponds inland. Twenty-three species were identified, only seven of which were present at all sampling sites. Shannon's diversity and Pielou's evenness indices revealed higher values in the spring and autumn; activity indices were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…Some illustrations made with the method of the present paper, were already published in other articles about terrestrial isopods: figure 1 in Medini-Bouaziz et al (2006); figure 2 in Montesanto et al (2007); figures 2, 3 in Montesanto et al (2008); figures 1–5 in Montesanto et al (2011); figures 1, 2 in Messina et al (2011); figure 1 in Messina et al (2012); figures 6, 7, and 9 in Montesanto et al (2012); figure 1 in Lupetti et al (2013); figures 2, 3 in Montesanto et al (2013); figures 1–6 in Messina et al (2014). Some indications about drawing terrestrial isopods for taxomomic papers are reported in Figure 7, whereas magnifications show the differences of the brush size for different anatomical parts.…”
Section: Resultsmentioning
confidence: 70%
“…Some illustrations made with the method of the present paper, were already published in other articles about terrestrial isopods: figure 1 in Medini-Bouaziz et al (2006); figure 2 in Montesanto et al (2007); figures 2, 3 in Montesanto et al (2008); figures 1–5 in Montesanto et al (2011); figures 1, 2 in Messina et al (2011); figure 1 in Messina et al (2012); figures 6, 7, and 9 in Montesanto et al (2012); figure 1 in Lupetti et al (2013); figures 2, 3 in Montesanto et al (2013); figures 1–6 in Messina et al (2014). Some indications about drawing terrestrial isopods for taxomomic papers are reported in Figure 7, whereas magnifications show the differences of the brush size for different anatomical parts.…”
Section: Resultsmentioning
confidence: 70%
“…The numbers assigned to the traps, the distances between the traps, and the orientation of each transect are indicated in Messina et al (2011). The traps were emptied monthly, and the collected material was transferred to 70% alcohol solutions.…”
Section: Samplingmentioning
confidence: 99%
“…Among these, David et al (1999) evaluated the relationship between diplopods and isopods and the vegetation structure in southern France; Sfenthourakis (1992); Sfenthourakis et al (2005Sfenthourakis et al ( , 2008 studied the habitat preference in natural areas in Greek mountains; Souty-Grosset et al (2008) reported the relationships among habitats, plant components and communities of terrestrial isopods in the Region Poitou-Charentes (France). A study has already been conducted on the diversity of isopods in the Natural Reserve of Vendicari (Messina et al 2011) that is characterized by salty coastal lakes (ponds). In this area 23 species were identified, 3 of which were new to this area: Spelaeoniscus sp., Bathytropa sp., Agabiformius lentus.…”
Section: Introductionmentioning
confidence: 99%
“…In Sicily, some studies on the diversity, systematics and geographical distribution of terrestrial isopods have been conducted (Vandel 1969;Caruso et al 1987), and recently, research has focused on terrestrial isopod communities of the coastal humid areas (Messina et al 2011(Messina et al , 2012(Messina et al , 2014(Messina et al , 2015. Several studies have shown that distribution and abundance are influenced by social factors (Devigne et al 2011;Broly et al 2015) and environmental variables, such as weather, costal zonation, and plant associations (David et al 1999;Zimmer 2004;Antunes et al 2008;Souty-Grosset et al 2008;Morón-Ríos et al 2010;Hamaied-Melki et al 2011;Khemaissia et al 2011Khemaissia et al , 2012.…”
Section: Introductionmentioning
confidence: 99%